Ultramodern Underground Dallas: Vincent Ponte’s Pedestrian-Way as Systematic Solution to the Declining Downtown - Terranova, Charissa (Urban History Review / Revue d'histoire urbaine, 2009)
AbstractMid last century, North American civil servants and urban planners and developers proffered inventive solutions to the problem of the declining downtown core. Robert Moses looked to super-block development and Title 1 of the US Housing Act of 1949 to funnel federal dollars into urban renewal projects in New York City. Because it had been successful in the suburbs, Victor Gruen sought retail development in the form of downtown shopping centres. The Montreal-based planner Vincent Ponte focused his attention on the “multi-level city centre.” Similar to the solutions proffered by Gruen and Moses, Ponte’s multi-level centres were large-scale and multi-use. However, unlike his colleagues’ tabula rasa interventions, Ponte’s multi-level centre was incremental. This essay focuses on Ponte’s little-known 1969 multi-level pedestrian-way plan for downtown Dallas. I argue that Ponte’s project for the centre of Dallas is unique in Ponte’s oeuvre because, departing from his own espousal of super-block development, it was not built in one fell swoop within a super-block. The multi-level megastructural pedestrian-way in Dallas was fluid and incremental in its original planning and subsequent evolution. It is best understood according to Ponte’s instrumentalization of systems theory.